What children with and without ASD see: Similar visual experiences with different pathways through parental attention strategies. (December 2022) - Perkovich, Elizabeth; Sun, Lichao; Mire, Sarah; Laakman, Anna; Sakhuja, Urvi; Yoshida, Hanako
Background and aims: Although young children's gaze behaviors in experimental task contexts have been shown to be potential biobehavioral markers relevant to autism spectrum disorder (ASD), we know little about their everyday gaze behaviors. The present study aims (1) to document early gaze behaviors that occur within a live, social interactive context among children with and without ASD and their parents, and (2) to examine how children's and parents' gaze behaviors are related for ASD and typically developing (TD) groups. A head-mounted eye-tracking system was used to record the frequency and duration of a set of gaze behaviors (such as sustained attention [SA] and joint attention [JA]) that are relevant to early cognitive and language development. Methods: Twenty-six parent–child dyads (ASD group = 13, TD group = 13) participated. Children were between the ages of 3 and 8 years old. We placed head-mounted eye trackers on parents and children to record their parent- and child-centered views, and we also recorded their interactive parent–child object play scene from both a wall- and ceiling-mounted camera. We then annotated the frequency and duration of gaze behaviors (saccades, fixation, SA, and JA) for different regions of interest (object, face, and hands), and attention shifting. Independent group t-tests and ANOVAs were used to observe group comparisons, and linear regression was used to test the predictiveness of parent gaze behaviors for JA. Results: The present study found no differences in visual experiences between children with and without ASD. Interestingly, however, significant group differences were found for parent gaze behaviors. Compared to parents of ASD children, parents of TD children focused on objects and shifted their attention between objects and their children's faces more. In contrast, parents of ASD children were more likely to shift their attention between their own hands and their children. JA experiences were also predicted differently, depending on the group: among parents of TD children, attention to objects predicted JA, but among parents of ASD children, attention to their children predicted JA. Conclusion: Although no differences were found between gaze behaviors of autistic and TD children in this study, there were significant group differences in parents' looking behaviors. This suggests potentially differential pathways for the scaffolding effect of parental gaze for ASD children compared with TD children. Implications: The present study revealed the impact of everyday life, social interactive context on early visual experiences, and point to potentially different pathways by which parental looking behaviors guide the looking behaviors of children with and without ASD. Identifying parental social input relevant to early attention development (e.g., JA) among autistic children has implications for mechanisms that could support socially mediated attention behaviors that have been documented to facilitate early cognitive and language development and implications for the development of parent-mediated interventions for young children with or at risk for ASD. Note: This paper uses a combination of person-first and identity-first language, an intentional decision aligning with comments put forth by Vivanti (Vivanti, 2020), recognizing the complexities of known and unknown preferences of those in the larger autism community.